Advances in food packaging technology-A review - Nura , Abdullahi (Journal of Postharvest Technology, 2018)
Food packaging industry involve a number of actors which include producers, retailers, consumers and researchers. Each of the actors in the cycle has a legitimate priority to protect. The primary aim of all the players is to protect the food from degradation by environmental and human factors and also ensure delivery of food items to ultimate consumers in safe and sound condition. In addition to protection, food package also serves as means of communication between producer and consumer by carrying vital information about the content specification, producer’s information, product handling tips and storage requirements. It requires that during containment the package should behave inert and prevent chemical migration between the package and the food. The materials that are commonly used in food packaging are glass, metals papers and plastics. Numerous laminates and coatings with different physical, chemical and barrier properties were developed from these traditional packaging materials. This paper reviews recent innovations in food packaging technology with emphases on principles and applications of active and intelligent packaging, nanotechnology, antimicrobial packaging, edible coatings and films and sustainable packaging.